2014
DOI: 10.1080/09585192.2014.936235
|View full text |Cite
|
Sign up to set email alerts
|

Ideas at work

Abstract: The purpose of this article is to highlight the role of ideas in shaping the form, dynamics and products of the employment relationship. This article differentiates between different types of ideas, emphasizes the various types of agency that are involved in the creation, maintenance and defence of ideas and identifies a number of mechanisms that help to understand how actors promote ideas, how ideas gain broader prominence and how ideas change. Finally, we discuss the importance of context and resources in sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 52 publications
1
39
0
Order By: Relevance
“…Such actors include not only HR managers, but also professional associations, consultants, academics and other opinion leaders. This way, we could gain more fine-tuned insights to how ideas travel and disseminate (Hauptmeier and Heery, 2014), how different HR actors seek to legitimise their ideas (e.g. Pohler and Willness, 2014) and use influence tactics, often without formal authority.…”
Section: Discussion: New Directions For Hrm Researchmentioning
confidence: 99%
“…Such actors include not only HR managers, but also professional associations, consultants, academics and other opinion leaders. This way, we could gain more fine-tuned insights to how ideas travel and disseminate (Hauptmeier and Heery, 2014), how different HR actors seek to legitimise their ideas (e.g. Pohler and Willness, 2014) and use influence tactics, often without formal authority.…”
Section: Discussion: New Directions For Hrm Researchmentioning
confidence: 99%
“…Specifically, in some cases occupational ideology appears to cause particular responses (seen most often with clergy but also at times with actors) while in other cases occupational ideology appears to be drawn on, in both accommodating to the working environment and generating satisfaction. Therefore, such questions can be asked of other workers where some occupational ideology is required or is 'called up', and locates our work within the same supposition as Hauptmeier and Heery (2014), that ideas can cause tangible workplace outcomes. As they emphasise, it is important to specify under which conditions ideas matter.…”
Section: Discussionmentioning
confidence: 99%
“…Hoffmann (2009) went on to study homecare workers and found they were willing to work unpaid from a sense of self-sacrificial loyalty and to realise self-worth. Hoffman notes these dimensions as affecting willingness to resist poor terms and conditions, returning us again to the importance of identifying causal effects of ideas in the workplace (Hauptmeier and Heery, 2014). This is implicit in a question posed by Donaghey et al (2011) in relation to one aspect of their dialectical interpretation of employee silence.…”
Section: Ideology and Connections To Loyaltymentioning
confidence: 99%
See 1 more Smart Citation
“…Second, causal beliefs (Goldstein & Keohane, , p. 10) about cause–effect relationships define grievances and specific strategies for how such a policy paradigm can be achieved. Both these types of ideas are grounded in normative principled beliefs , which help “actors judge how the world ought to be and provide them with a moral compass” (Hauptmeier & Heery, , p. 2475). Principled beliefs strongly motivate collective action.…”
Section: Employers' Organisations As Social Movementsmentioning
confidence: 99%